2016
DOI: 10.1111/jsr.12431
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sleep deprivation on leadership behaviour in military officers: an experimental study

Abstract: While several studies show that leaders frequently lack sleep, little is known about how this influences leadership behaviour. The present study encompasses an experiment that investigated how three main types of leadership behaviour: transformational (four sub-facets); transactional (two sub-facets); and passive-avoidant (two sub-facets) leadership differed across a rested and a long-term, partially sleep-deprived condition. A total of 16 military naval officers participated. In both conditions, the leaders m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…Antecedents of destructive leadership initially received less attention than the potential outcomes, but this has changed dramatically over the past five years (Tepper et al, 2017;Zhang & Bednall, 2015). Possible antecedents range from micro-level to macro-level factors, such as supervisor personality traits (Eissa & Lester, 2017) and stress caused by climate conditions (Van de Vliert, Matthiesen, Gangsøy, Landro, & Einarsen, 2010) to antecedents in the military context like lack of sleep (Olsen, Pallesen, Torsheim, & Espevik, 2016). In a recent meta-analysis, Zhang and Bednall (2015) categorised antecedents into four main groups: supervisor-related, organization-related and subordinate-related antecedents, in addition to, demographic characteristics of supervisors and subordinates.…”
Section: Antecedents Outcomes and Prevalence Of Destructive Leadershipmentioning
confidence: 99%
See 2 more Smart Citations
“…Antecedents of destructive leadership initially received less attention than the potential outcomes, but this has changed dramatically over the past five years (Tepper et al, 2017;Zhang & Bednall, 2015). Possible antecedents range from micro-level to macro-level factors, such as supervisor personality traits (Eissa & Lester, 2017) and stress caused by climate conditions (Van de Vliert, Matthiesen, Gangsøy, Landro, & Einarsen, 2010) to antecedents in the military context like lack of sleep (Olsen, Pallesen, Torsheim, & Espevik, 2016). In a recent meta-analysis, Zhang and Bednall (2015) categorised antecedents into four main groups: supervisor-related, organization-related and subordinate-related antecedents, in addition to, demographic characteristics of supervisors and subordinates.…”
Section: Antecedents Outcomes and Prevalence Of Destructive Leadershipmentioning
confidence: 99%
“…A study of naval officers showed that ratings of military performance as a naval academy midshipman were predictive of laissez-faire leadership as an officer four to ten years after graduation (Yammarino, Spangler, & Bass, 1993). Olsen et al (2016) examined the influence of sleep on leadership behaviour and found that scores on laissez-faire behaviour increased from a rested to a sleep-deprived state, while Johnsen, Eid, Pallesen, Bartone, and Nissestad (2009) found that laissez-faire was associated with poorer military development grades and leadership effectiveness. Hence, destructive leadership appears to be associated with lack of sleep, lack of moral competency, low military competence and leadership effectiveness, in addition to low personality trait scores for hardiness.…”
Section: Descriptive Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A short break of just a few minutes every 60‐90 minutes—perhaps coinciding with a new section of the MDT discussions—not only refreshes team members but makes them more alert and able to continue and has been shown to be effective in many other working environments …”
Section: Personal Factors That Can Lead To Distractionmentioning
confidence: 99%
“…More specific to a focus on passive leadership, Barling & Dionisi () showed that cognitive distraction predicted passive leadership (but not abusive supervision). More recently, a study of 16 military naval officers who were randomly assigned in counterbalanced order to a rested or partially sleep‐deprived condition showed higher levels of passive‐avoidant and laissez‐faire leadership (and lower levels of transformational leadership) in the partially sleep‐deprived condition (Olsen, Pallesen, Torsheim, & Espevik, ). Thus, we predict thatHypothesis Daytime sleepiness predicts passive leadership.…”
Section: Theoretical Backgroundmentioning
confidence: 99%